2014
DOI: 10.1002/ana.24238
|View full text |Cite
|
Sign up to set email alerts
|

New brain infarcts on magnetic resonance imaging after coronary artery bypass graft surgery: Lesion patterns, mechanism, and predictors

Abstract: Post-CABG new brain infarcts are mostly silent and cortically located. Old age, aortic arch atherosclerosis, use of cardiopulmonary bypass, and systemic inflammatory response may contribute to the pathogenesis of post-CABG new brain infarcts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 43 publications
2
27
0
Order By: Relevance
“…The vast majority of these cardioembolic strokes involve lesions in a cortical territory. 50 In contrast, lacunar stroke is by definition restricted to a subcortical location. 51 About half of cardioembolic strokes involve multiple cerebral arterial territories (i.e., both internal cerebral arteries or one internal cerebral artery as well as the basilar artery), 50 which distinguishes cardiac embolism from artery-to-artery embolism due to large-artery atherosclerosis in the cerebral circulation.…”
Section: Diagnostic Criteria For Cardioembolic Strokementioning
confidence: 99%
“…The vast majority of these cardioembolic strokes involve lesions in a cortical territory. 50 In contrast, lacunar stroke is by definition restricted to a subcortical location. 51 About half of cardioembolic strokes involve multiple cerebral arterial territories (i.e., both internal cerebral arteries or one internal cerebral artery as well as the basilar artery), 50 which distinguishes cardiac embolism from artery-to-artery embolism due to large-artery atherosclerosis in the cerebral circulation.…”
Section: Diagnostic Criteria For Cardioembolic Strokementioning
confidence: 99%
“…After 30 min tHI, the ipsilateral hemisphere showed poorer recovery of SaO 2 than the contralateral cortex (~28% compared with ~39% in normoxia and ~53% versus ~70% under 100% oxygen) (Figure 1D) (n>3 times). This pattern suggests that a transient episode of HI may impair subsequent cortical oxygenation 5 .…”
Section: Resultsmentioning
confidence: 94%
“…A recent study showed that 27.5% of CABG patients developed new brain infarct on diffusion-weighted imaging (DWI). Among them, 3.1% showed overt symptoms while the other 24.1% were clinically silent 5 . This high rate of silent infarct may relate to the phenomenon of post-surgery decline of cognitive functions 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the strong circumstantial evidence favouring an embolic aetiology of most cryptogenic strokes,3 4 investigators have recently used the term embolic stroke of undetermined source (ESUS) to describe non-lacunar stroke without evidence of ipsilateral extracranial or intracranial large artery stenosis of 50% or more, a major cardioembolic source such as atrial fibrillation (AF) or other specific mechanism of stroke 5. Identifying the root cause of ischaemic stroke is more than an academic issue, since the specific stroke subtype often guides secondary stroke prevention measures.…”
Section: Introductionmentioning
confidence: 99%